Laparo-endoscopic Approach for Large Ovarian Cyst in the Morbidly Obese: Case Report - Goh, Wei-An; Tan, Eunice MX; Nadarajah (MRCOG), Ravichandran (International Journal of Innovative Research in Medical Science, 2021)
We report a successful case of laparo-endoscopic single site total hysterectomy and bilateral salpingo-oophorectomy (LESS THBSO) using conventional laparoscopic instruments for a large ovarian cyst in a morbidly obese woman. A 58-year-old female with a BMI of 46kg/m2 complaint of abdominal distension. A pelvic ultrasound revealed a left ovarian cyst measuring 21.3 x 15.2 x 20.8 cm. The IOTA score is 3.5% and the RMI score was 51, suggesting a benign pathology. LESS THBSO was performed and the final histology was a benign ovarian mucinous cystadenoma. The patient recovered well with no postoperative complications. This case demonstrates that LESS is feasible for large ovarian cysts even in morbidly obese patients when appropriate cases are selected and when the patient is managed in a multi-disciplinary team.